The role of perspective-taking in suppressing stereotypes about mathematics - Mana Yamamoto; Takashi Oka (BMC Research Notes, 2023)
Abstract Objective When people attempt to suppress stereotypes, they often end up making stereotypical judgments. The adverse effects of this form of suppression are called “paradoxical effects.” This study examined the effect of perspective-taking as a strategy to reduce the paradoxical effects related to stereotype suppression. Specifically, this study addressed stereotypes within the context of women’s mathematical abilities, with Japanese university students as participants. It was predicted that when participants suppressed the stereotype of a woman, those who engaged in perspective-taking toward that woman would make less stereotypical judgments of other women, compared with those who did not. Moreover, as this study focuses on gender stereotypes, an exploratory analysis was conducted to investigate whether the effects of engaging in perspective-taking about women vary depending on the participants’ gender. Results Although no significant effect was observed and the hypothesis was not supported, and while the results of this study were statistically inadequate, they suggest that among the female participants, those who did not engage in perspective-taking showed the paradoxical effects of stereotype suppression. However, those paradoxical effects were not observed among those who performed perspective-taking.